Evaluation of the Recovery Supplemental Feeding Program (PMT-P) for 90 Days on the Acceleration of Reducing Cases of Stunting Toddlers in the Working Area of Wanadadi Community Health Center 2 - Shoofia Rihadhatul Aisy; Mardiana Mardiana (Sport and Nutrition Journal, 2025)
Stunting is a growth disorder (body and brain growth) caused by ongoing malnutrition, which causes children to be shorter than normal children of their age and have delays in thinking. One of the direct causes of stunting is intake. In an effort to accelerate the reduction of stunted cases, the Banjarnegara District Health Service, in collaboration with 35 Community Health Centers (Puskesmas) in Banjarnegara District, is implementing a program to provide supplementary feeding (PMT-P) for 90 days to stunted and malnourished toddlers. Objective: To determine the implementation of the Recovery Supplemental Feeding Program (PMT-P) for 90 days to accelerate the reduction in stunting for toddlers in the work area of Wanadadi Community Health Center 2. Method: Qualitative research using informant sampling techniques, including purposive sampling and snowball sampling. Result: the implementation of the additional recovery food program in the Wanadadi 2 Community Health Center working area has not been running optimally. Based on the three stages that influence program implementation, there is one variable that is the main point of the problem, namely, the process stage. This process stage encompasses planning, which includes coordination, mobilization, and implementation, all of which involve distribution, counseling, and socialization.